1997
DOI: 10.1007/bf00942046
|View full text |Cite
|
Sign up to set email alerts
|

DNA aberrations in urinary bladder cancer detected by flow cytometry and FISH

Abstract: Detection of molecular alterations is of potential significance for diagnosis and prognosis in bladder cancer. Fluorescence in situ hybridization (FISH) allows visualization and quantitation of genes and chromosomes on a cell by cell level and can easily be applied to urinary cells. To evaluate the sensitivity of FISH for detection of DNA aberrations in bladder cancer, formalin-fixed tissues of 293 tumors were examined by FISH and flow cytometry (FCM). Centromere probes for the chromosomes X, Y, 1, 7, 9, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 17 publications
(31 reference statements)
1
18
0
2
Order By: Relevance
“…14,36 However, there is a point of diminishing returns at which the inclusion of additional probes does not provide significant increases in the overall sensitivity of the assay. 36 Furthermore, it is currently not possible to have more than four different visually distinguishable fluorophores in a single FISH probe set due to spectral overlap in the excitation and emission spectra of the different fluorescent labels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,36 However, there is a point of diminishing returns at which the inclusion of additional probes does not provide significant increases in the overall sensitivity of the assay. 36 Furthermore, it is currently not possible to have more than four different visually distinguishable fluorophores in a single FISH probe set due to spectral overlap in the excitation and emission spectra of the different fluorescent labels.…”
Section: Discussionmentioning
confidence: 99%
“…14,36 However, there is a point of diminishing returns at which the inclusion of additional probes does not provide significant increases in the overall sensitivity of the assay. 36 Furthermore, it is currently not possible to have more than four different visually distinguishable fluorophores in a single FISH probe set due to spectral overlap in the excitation and emission spectra of the different fluorescent labels. Because the goal of this study was to identify a four-probe set that would provide optimal sensitivity and specificity for the detection of dysplasia and esophageal adenocarcinoma in patients with Barrett's esophagus, ROC curves for various fourprobe combinations were performed.…”
Section: Discussionmentioning
confidence: 99%
“…For the slides prepared from adjacent normal-appearing bronchial tissue, only those uncontaminated by tumor cells were processed for further FISH analysis. Dualcolor FISH was done using a digoxigenin-labeled SP-A probe as described by our previous publication (29), and a CEP10 was used as an internal reference.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that fluorescently labeled probes of chromosomes 3, 7, 17 and 9 could detect bladder UC as a non-invasive and sensitive test [5,6,7,9,10,14,15,16,17,18,19,20,21,22]. To date, few groups reported their studies on the utility of FISH in the detection of UUT-UC [23,24,25].…”
Section: Discussionmentioning
confidence: 99%